GENETICS OF THE POLYCYSTIC OVARY SYNDROME - KOSOVA, Gülüm (2012)
Polycystic ovary syndrome (PCOS) is a highly complex endocrine disorder, characterized by hyperandrogenemia, menstrual irregularities and polycystic ovaries. A strong genetic component to the etiology of PCOS is evident. However, due to the genetic and phenotypic heterogeneity of PCOS and the lack of insufficiently large cohorts, studies to identify specific contributing genes to date have yielded only few conclusive results. In this review we discuss the currnt status of the genetic analysis of PCOS including the results of numerous association studies with candidate genes involved in TGF-β and insulin signaling, type 2 diabetes mellitus and obesity susceptibility. Furthermore, we address current challenges in genetic studies of PCOS, and the promise of new approaches, including genome-wide association studies and next-generation sequencing.